2007
DOI: 10.1016/j.stem.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Fate Analysis Reveals the Multipotent and Self-Renewal Capacities of Sox2+ Neural Stem Cells in the Adult Hippocampus

Abstract: To characterize the properties of adult neural stem cells (NSCs), we generated and analyzed Sox2-GFP transgenic mice. Sox2-GFP cells in the subgranular zone (SGZ) express markers specific for progenitors, but they represent two morphologically distinct populations that differ in proliferation levels. Lentivirus- and retrovirus-mediated fate-tracing studies showed that Sox2+ cells in the SGZ have potential to give rise to neurons and astrocytes, revealing their multipotency at the population as well as at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
710
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(756 citation statements)
references
References 41 publications
34
710
1
5
Order By: Relevance
“…16 Of note, Sox2 is highly expressed in the neurogenetic tissues, such as the hippocampus and central canal, and has a critical role in unperturbed neurogenesis. [17][18][19] These insights corroborate our interest in exploring the role of K11-linked polyubiquitin chain assembly machineries in fine-tuning the precise level of Sox2 in mES cells.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…16 Of note, Sox2 is highly expressed in the neurogenetic tissues, such as the hippocampus and central canal, and has a critical role in unperturbed neurogenesis. [17][18][19] These insights corroborate our interest in exploring the role of K11-linked polyubiquitin chain assembly machineries in fine-tuning the precise level of Sox2 in mES cells.…”
supporting
confidence: 60%
“…Interestingly, the importance of the interaction extends to the role of Ube2s in regulating ES cell differentiation to the neural ectoderm lineage. As Sox2 is important for neurogenesis in the adult central nerve system through its maintenance of neural stem and progenitor cells, [17][18][19] as a regulator of Sox2 ubiquitination, Ube2s may have yet unexplored role in regulating neurogenesis, and its dysfunction may be related to neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of neurons from neural progenitors in the adult DG has been proposed to take 2-4 weeks, but timing has been hampered by the experimental approaches used 6,14,19,29 . We analyzed the Hes5CreER T2 mice seven days (d7) and 3 weeks after TAM induction (d21; Fig.…”
Section: Hes5creermentioning
confidence: 99%
“…Previous works have demonstrated that cell cycle regulation in the adult brain is precursor-type-specific [24], thus we sought to determine whether the defect in proliferation observed in Cdk6 À/À brains was restricted to a subpopulation versus all cycling precursors. First, we used glial fibrillary acidic protein (GFAP) and the Sry-related HMG box transcription factor Sox2 to identify immature DG precursors with, respectively, radial (type 1) and nonradial (type 2a) morphology that are not yet restricted to a neuronal fate [25]. No significant differences in the number of proliferating GFAP þ (i.e., GFAP þ /Ki-67 þ ) nor Sox2 þ (i.e., Sox2 þ /Ki-67 þ ) precursors were found in Cdk6 À/À mice ( Fig.…”
Section: Cdk6 Selectively Regulates the Proliferation Of Neuronally Cmentioning
confidence: 99%